2013
DOI: 10.1016/j.lfs.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Type II diabetes promotes a myofibroblast phenotype in cardiac fibroblasts

Abstract: Aims Cardiovascular disease is the leading cause of death for individuals diagnosed with type II diabetes mellitus (DM). Changes in cardiac function, left ventricular wall thickness and fibrosis have all been described in patients and animal models of diabetes; however, the factors mediating increased matrix deposition remain unclear. The goal of this study was to evaluate whether cardiac fibroblast function is altered in a rat model of type II DM. Main methods Cardiac fibroblasts were isolated from 14 week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 31 publications
5
61
1
Order By: Relevance
“…Changes were relatively small, but included increased contractile behaviour, increased SMA and type I collagen expression and increased cell proliferation in the diabetic cells [17]. Very recently, in a study using a murine model of T2DM (db/db mouse), CF derived from db/db hearts were shown to have elevated expression of several pro-fibrotic markers (type I collagen, PAI-1, TGF-, TIMP-2) compared with cells derived from db/wt littermates [18].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Changes were relatively small, but included increased contractile behaviour, increased SMA and type I collagen expression and increased cell proliferation in the diabetic cells [17]. Very recently, in a study using a murine model of T2DM (db/db mouse), CF derived from db/db hearts were shown to have elevated expression of several pro-fibrotic markers (type I collagen, PAI-1, TGF-, TIMP-2) compared with cells derived from db/wt littermates [18].…”
Section: Discussionmentioning
confidence: 94%
“…Using fibroblasts cultured from the hearts of Zucker diabetic rats, a laboratory model of T2DM, it was recently demonstrated that diabetic cells adopt a more myofibroblast-like phenotype compared with cells derived from lean control hearts [17]. Changes were relatively small, but included increased contractile behaviour, increased SMA and type I collagen expression and increased cell proliferation in the diabetic cells [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, AGE-modified proteins can induce CF proliferation and collagen production in an angiotensin II-dependent manner [23]. Several recent studies on CF derived from type 2 diabetic patients or diabetic animal models have reported that fibroblasts from diabetic hearts possess an inherent pro-fibrotic phenotype, including elevated collagen synthesis, myofibroblast transdifferentiation and, in some cases, upregulation of RAGE expression [24,78,129,130].…”
Section: Age-modified Collagenmentioning
confidence: 99%
“…1,2 The structural changes included fibrosis, apoptosis, and angiopathy of myocytes, and the functional changes included endothelium-myocytes uncoupling, impairment of contractility of cardiomyocytes, decrease in survival and differentiation of cardiac stem cells, and diastolic and systolic dysfunction. [3][4][5] Nonetheless, the pathophysiology of DCM remains uncertain and novel therapeutic strategies for its prevention and rescue are urgently needed.…”
Section: Introductionmentioning
confidence: 99%